2016
DOI: 10.3389/fmicb.2016.01716
|View full text |Cite
|
Sign up to set email alerts
|

Changes of the Bacterial Abundance and Communities in Shallow Ice Cores from Dunde and Muztagata Glaciers, Western China

Abstract: In this study, six bacterial community structures were analyzed from the Dunde ice core (9.5-m-long) using 16S rRNA gene cloning library technology. Compared to the Muztagata mountain ice core (37-m-long), the Dunde ice core has different dominant community structures, with five genus-related groups Blastococcus sp./Propionibacterium, Cryobacterium-related., Flavobacterium sp., Pedobacter sp., and Polaromas sp. that are frequently found in the six tested ice layers from 1990 to 2000. Live and total microbial d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 64 publications
(114 reference statements)
3
11
0
Order By: Relevance
“…Members belonging to the genus Methylobacterium were also reported to dominate the microbial community in ancient ice cores from many previous studies ( Miteva, 2008 ; Segawa et al, 2010 ; Antony et al, 2012 ; Miteva et al, 2015 , 2016 ), including several microbial investigations of the Guliya ice cap ice cores using culture-dependent methods ( Christner et al, 2000 , 2001 ; Christner, 2003 ). Five other genera with relative abundances of 0.1–4.5%, which had recognized names, were also previously reported to be abundant in glacier ice cores, including the genera Flavobacterium ( Liu et al, 2015 ; Chen et al, 2016 ), Janthinobacterium ( Christner, 2003 ; Miteva, 2008 ), Polaromonas ( Liu et al, 2009 ; An et al, 2010 ; Chen et al, 2016 ), Sphingomonas ( An et al, 2010 ; Miteva et al, 2016 ), and Rhodobacter ( Liu et al, 2015 ). The detection of bacterial sequences belonging to similar genera in ice core samples from different glaciers located around the world can be explained by the ubiquitous distribution of certain species in geographically distant environments ( Baas Becking, 1934 ; Martiny et al, 2006 ).…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Members belonging to the genus Methylobacterium were also reported to dominate the microbial community in ancient ice cores from many previous studies ( Miteva, 2008 ; Segawa et al, 2010 ; Antony et al, 2012 ; Miteva et al, 2015 , 2016 ), including several microbial investigations of the Guliya ice cap ice cores using culture-dependent methods ( Christner et al, 2000 , 2001 ; Christner, 2003 ). Five other genera with relative abundances of 0.1–4.5%, which had recognized names, were also previously reported to be abundant in glacier ice cores, including the genera Flavobacterium ( Liu et al, 2015 ; Chen et al, 2016 ), Janthinobacterium ( Christner, 2003 ; Miteva, 2008 ), Polaromonas ( Liu et al, 2009 ; An et al, 2010 ; Chen et al, 2016 ), Sphingomonas ( An et al, 2010 ; Miteva et al, 2016 ), and Rhodobacter ( Liu et al, 2015 ). The detection of bacterial sequences belonging to similar genera in ice core samples from different glaciers located around the world can be explained by the ubiquitous distribution of certain species in geographically distant environments ( Baas Becking, 1934 ; Martiny et al, 2006 ).…”
Section: Resultsmentioning
confidence: 77%
“…Thus, microorganisms immured in ice cores represent those in the atmosphere at the time of deposition and hence reflect environmental conditions during the same time period ( Priscu et al, 2007 ; Xiang et al, 2009 ). Previous investigations of the microbial community in polar glaciers (e.g., Miteva et al, 2009 , 2015 ; Santibanez-Avila, 2016 ) and low-latitude glaciers (e.g., Yao et al, 2008 ; Chen et al, 2016 ) have suggested that microbial diversity and abundance preserved in deep ice cores are correlated with dust particle concentrations, local climate conditions, and global atmospheric circulation. Usually the biomass is very low in most glacier ice samples, with the estimated number of microbial cells ranging from 10 2 to 10 4 cells ml -1 ( Miteva, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Antarctic permafrost (brown crosses) and subglacial sediments (brown-filled triangles) exhibit cell concentrations that are also greater than those of the adjacent and overlying ice sheets (open triangles). In general, cell concentrations in ice sheets (open squares, triangles, and circles) do not diminish as a function of depth and age as rapidly as observed for permafrost sediments and likely reflect a combination of airborne input flux and in situ metabolism (Chen et al, 2016). Cell concentrations are higher near rock-ice interfaces and in dust-rich ice, pointing to the importance of chemical and physical gradients.…”
Section: Modern Rock-hosted Life On Earthmentioning
confidence: 83%
“…Cryobacterium strains, within the family Microbacteriaceae , are Gram‐positive, non‐spore‐forming, irregular rod‐shaped, aerobic bacteria (Liu et al ., ). Cryobacterium strains were commonly discovered in cold environments, such as in ice core, surface soil and ice of mountain glaciers (Reddy et al ., ; Liu et al ., ; Chen et al ., ); the Antarctic, Arctic and Siberian permafrost soils (Suzuki et al ., ; Bajerski et al ., ; Schuerger and Nicholson, ); Antarctic sandy intertidal sediments (Yu et al ., ), surface seawater along the Victoria Land coast of Antarctica (Giudice et al ., ) and glacier cryoconite holes in the High Arctic (Singh et al ., ). Although the genus Cryobacterium is widespread in the cryosphere, it may be a rare taxon (Liu et al ., ).…”
Section: Introductionmentioning
confidence: 99%